Kemampuan Pemecahan Masalah Siswa pada Materi Barisan dan Deret Aritmatika - Afda Fawaida; Putri Nur Malasari; Fina Tri Wahyuni (JUMAT: Jurnal Matematika, 2024)
A student's skill in solving various problems using mathematical activities can be called mathematical problem solving ability. This research was carried out to determine students' skills in solving problems mathematically on Arithmetic Sequences and Series material. The researcher chose this type of qualitative descriptive research because the researcher wanted to get real data in the field. The research subjects were 17 students of class XI MIPA-B MA Darun Najah Pati for the 2023/2024 period. The researcher used a written test to collect data, using five essay questions, then an assessment was carried out to obtain a percentage at each stage and an average process was carried out. The analysis of this research refers to 4 levels according to Polya's theory, namely reading the problem, making a work plan, carrying out work design, and reinterpreting. Based on the analysis that has been carried out, it was found that 54.51% of students were able to read the problem, 47.84% were able to make work plans, 43.14% of students carried out work plans, and 21.89% of students could reinterpret problems. Based on the data obtained, it is stated that MA Darun Najah Pati students have medium category problem solving abilities.